Preventative releases of self-limiting Ceratitis capitata provide pest suppression and protect fruit quality in outdoor netted cages. Issue 2 (2nd April 2020) - Asadi, Romisa; Elaini, Rachid; Lacroix, Renaud; Ant, Thomas; Collado, Amandine; Finnegan, Lucy; Siciliano, Paolo; Mazih, Ahmed; Koukidou, Martha
Abstract: The Mediterranean fruit fly, Ceratitis capitata, (Medfly) is considered a key pest of citrus fruit in many countries. Integrated pest management (IPM) approaches are frequently highly dependent on the use of insecticides. Oxitec's self-limiting (prevents the insects' offspring from surviving to adulthood) Medfly technology (OX3864A) offers an approach to manage Medfly outbreaks and may offer improved sustainability and economics for area-wide programmes. Netted cages were used to evaluate OX3864A deployed for the first time outdoors as a preventative treatment to suppress wild Medfly. Comparative assessments examined sexual competitiveness, the relative performance of OX3864A releases at both adult and pupal life-stages, and the ability of OX3864A to protect against fruit damage. OX3864A males are as competitive as wild males. Deployment of both adult and pupal life-stages of OX3864A effectively reduce Medfly abundance, resulting in elimination of the target pest populations. OX3864A deployment as adults also demonstrated the beneficial attribute of protecting fruit quality to preserve marketable yield. Data for adult and pupal deployment strategies are encouraging for self-limiting technologies targeting Medfly populations and support a broader evaluation of OX3864A Medfly or further improved self-liming Oxitec strains of Medfly in open settings.